Morphometric characterization of Long-Legged Buzzard (Buteo rufinus) Tongue and Heart Caracterización - Saime Betül Baygeldi; Yeşim Aslan Kanmaz (Revista Científica)
Morphometric and scanning electron microscopic evaluations reveal limitations in long-legged buzzards (Buteo  rufinus), are particularly limited  when it comes  to the  detailed morphological characteristics of the tongue and heart. The aim of our study is to present these data in detail and to contribute to the anatomical formation of wild animals, which are particularly difficult to study. Four Long-Legged Buzzard (Buteo rufinus) belonging to the Accipitridae family were used in this study. The tongues and hearts of the animals were dissected and macro and micrometric analyses were performed. The tongue of the Long-Legged Buzzard was distinctly elongated, terminating in an oval-shaped apex. The tongue widths were 3.83±0.03mm at the apex lingua, 7.64±0.07mm at the corpus lingua and 9.09±0.04mm at the papillary apex. The total length of the tongue from the radix to the apex was 29.30±050 mm and the greatest thickness of the corpus was 2.89±16mm. The length of the Long-Legged Buzzard heart from the apex to the base was 30.05±0.05mm, the thickness of the base cordis was 25.03±0.16 mm and the thickness of the apex cordis was 10.95±0.09mm.